2017
DOI: 10.1161/jaha.116.003498
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatic Heart Disease Severity, Progression and Outcomes: A Multi‐State Model

Abstract: BackgroundRheumatic heart disease (RHD) remains a disease of international importance, yet little has been published about disease progression in a contemporary patient cohort. Multi‐state models provide a well‐established method of estimating rates of transition between disease states, and can be used to evaluate the cost‐effectiveness of potential interventions. We aimed to create a multi‐state model for RHD progression using serial clinical data from a cohort of Australian patients.Methods and ResultsThe No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 24 publications
3
69
0
Order By: Relevance
“…It was found that the presence of severe disease indicated the need for surgical intervention in up to 50% by 2 years. In the same study, it was shown that 10% of patients with severe RHD were dead within 6 years [7]. This data emphasises that surgery is the only treatment that prevents death in patients with severe RHD.…”
Section: Discussionmentioning
confidence: 77%
“…It was found that the presence of severe disease indicated the need for surgical intervention in up to 50% by 2 years. In the same study, it was shown that 10% of patients with severe RHD were dead within 6 years [7]. This data emphasises that surgery is the only treatment that prevents death in patients with severe RHD.…”
Section: Discussionmentioning
confidence: 77%
“…A separate analysis was done looking at the potential health effects and economic outcomes of improved adherence to secondary prophylaxis. For modeling purposes, we analyzed the potential effect of increasing adherence to 100%, which, by reducing ARF recurrences, we hypothesized may result in the following improvements in disease progression: Mild RHD remains mild (does not progress to moderate or severe disease). Moderate RHD: (a) A 50% reduction in progression is shown from moderate to severe disease or surgery (in our current practice model, ≈29% currently progress over 10 years since diagnosis, so our improved prophylaxis model allowed 15% to progress, with the other 14% remaining moderate); (b) other transitions from the moderate state remain the same. Severe RHD showed no change to observed disease progression. …”
Section: Methodsmentioning
confidence: 99%
“…shown from moderate to severe disease or surgery (in our current practice model, %29% currently progress over 10 years since diagnosis, 9 so our improved prophylaxis model allowed 15% to progress, with the other 14% remaining moderate); (b) other transitions from the moderate state remain the same. 3.…”
Section: Moderate Rhd: (A) a 50% Reduction In Progression Ismentioning
confidence: 99%
“…Disease severity varies over time, when workers [33] used a multistage model in which surgeries and deaths were evaluated in 591 patients with RHD, one half of cases with severe disease proceeded to valve surgery by 2 years, and 10% were dead within 6 years. Those diagnosed with moderate RHD, had a similar chance of disease regression or progression over time.…”
Section: Journal Of Preventive Medicine Issn 2572-5483mentioning
confidence: 99%